Potential of Forest Fire in BKPH Dander, KPH Bojonegoro, East Java - Bambang Hero Saharjo; Rizkia Ajeng Setya Wintanti (Jurnal Silvikultur Tropika, 2022)
The potential of forest fires in BKPH Dander KPH Bojonegoro can be assessed based on forest fires sourse, the control efforts, and rainfall. This study aims to analyze the source of forest fires and the control efforts done by BKPH Dander, and analyze the level of vulnerability of forest fires based on rainfall. The data used is divided into primary data and secondary data. Average annual rainfall in last 5 years is 1 788.8 mm/years with total area of forest fires 44.66 Ha and total loss approximately Rp5.645.300. The potential of forest fires based on land clearing in BKPH Dander are medium, meanwhile the potential by conflict caused of the burning activity by some perpetrator with their own circumstances and for thair needs. Optimalization the control effort of forest fires showing good result, it caused by the cooperation of community's high awarness and participation to protect and sustaining forest environment. Keywords: Community participation, Forest fire, KPH Bojonegoro, prevention, potency.